2019
DOI: 10.23887/jppsi.v1i1.21916
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Model Problem Based Learning Terhadap Keterampilan Berpikir Kritis Siswa Kelas Vii SMP Pada Pembelajaran Ipa

Abstract: Penelitian ini bertujuan menganalisis perbedaan keterampilan berpikir kritis antara siswa yang dibelajarkan dengan model problem based learning (PBL) dan model pembelajaran kooperatif tipe student team achievement division (STAD). Penelitian ini merupakan penelitian eksperimen semu dengan rancangan nonequivalent pretest-posttest control group design. Populasi penelitian adalah seluruh siswa kelas VII SMP Negeri 6 Singaraja tahun ajaran 2017/2018 yang berjumlah 304 orang yang tersebar ke dalam 11 kelas. Sampel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Such example on study in 2015 also concluded that this model was able to improve students' critical thinking skills (Simbolon & Tapilouw, 2015). Dharma et al (2019) found that problembased learning model has a positive impact that the critical thinking skills of a group of students combined with cooperative learning model of STAD. In 2019 for instance there is such a research on the implementation of problem-based learning model that help students in critical thinking, moreover student also become more active within the classroom learning practices (Sunarti & Fadilah, 2019).…”
Section: The Impact Of Problem-based Learning Model In Junior High School In Indonesia Year 2010-2019mentioning
confidence: 96%
“…Such example on study in 2015 also concluded that this model was able to improve students' critical thinking skills (Simbolon & Tapilouw, 2015). Dharma et al (2019) found that problembased learning model has a positive impact that the critical thinking skills of a group of students combined with cooperative learning model of STAD. In 2019 for instance there is such a research on the implementation of problem-based learning model that help students in critical thinking, moreover student also become more active within the classroom learning practices (Sunarti & Fadilah, 2019).…”
Section: The Impact Of Problem-based Learning Model In Junior High School In Indonesia Year 2010-2019mentioning
confidence: 96%
“…Menggunakan prosedur yang benar (true) dan dijelaskan dengan penalaran yang sahih (valid) dapat dihasilkan kesimpulan yang betul (truth) (Sihwinedar, 2015). Sutama, Arnyana & Swasta, 2014) menyatakan bahwa IPA atau yang sering disebut Sains memiliki fungsi yang fundamental dalam menimbulkan atau mengembangkan kemampuan berpikir kritis, kreatif, dan inovatif. Pembelajaran IPA harus senantiasa dapat melibatkan siswa, sehingga dapat tercapainya tujuan pembelajaran serta dapat merangsang siswa berpikir kritis, kreatif, dan inovatif.…”
Section: Pendahuluanunclassified
“…Menurut Dharma et al, (2019), kemampuan berpikir keritis sejak dini dapat diidentifikasi melalui empat indicator diantaranya 1. Berpikir simbolik (manipulasi objek); 2.…”
Section: Pendahuluanunclassified